Strategy Digital Transformation in The Management of Evidence and Polished Items by The State at The Bandar Lampung State Attorney - Febrina, Ira; Sobri, Kiagus Muhammad; Lionardo, Andries; Putra, Raniasa (Journal Public Policy, 2025)
This study aims to analyze the digital transformation strategy in the management of motorcycle crime evidence at the Bandar Lampung District Attorney's Office. The method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that the management of evidence was still not optimal, marked by the large number of evidence that was damaged or lost due to a lack of professionalism in safeguarding. The findings identified several key issues, including an unbalanced number of units, limited storage facilities, and a lack of qualified human resources. The research emphasized the importance of digital transformation that not only speeds up processes, but also increases transparency and accountability in evidence management. The conclusion of this study is that the implementation of digital strategies is necessary to overcome the challenges, as well as to improve the efficiency and effectiveness of evidence management. It is hoped that future research can explore more deeply the implementation of specific technologies that can assist in the management of evidence in other law enforcement agencies.